2017
DOI: 10.20858/tp.2016.11.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Driving Cycle Optimisation on the Highway

Abstract: Summary. This paper is devoted to the problem of reducing vehicle energy consumption. The authors consider the optimisation of highway driving cycle a way to use the kinetic energy of a car more effectively at various road conditions. The model of a vehicle driving control at the highway which consists of elementary cycles, such as accelerating, free rolling and deceleration under forces of external resistance, was designed. Braking, as an energy dissipation regime, was not included. The influence of the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The authors showed that for given road conditions there is an optimal value of speed at which fuel consumption is minimal. This statement can also be agreed with, taking into account the known developments of energy-saving transport cycles [18]. However, such statements are accepted for instantaneous speeds in the absence of forced braking/acceleration.…”
Section: Literature Review and Problem Statementmentioning
confidence: 87%
See 1 more Smart Citation
“…The authors showed that for given road conditions there is an optimal value of speed at which fuel consumption is minimal. This statement can also be agreed with, taking into account the known developments of energy-saving transport cycles [18]. However, such statements are accepted for instantaneous speeds in the absence of forced braking/acceleration.…”
Section: Literature Review and Problem Statementmentioning
confidence: 87%
“…However, the researchers did not form a clear restriction on the implementation of the traffic schedule. The developed algorithm offers optimal transport cycles, not taking into account that along the highway such cycles can have different lengths and structures [18]. Therefore, the given algorithm is not quite suitable for the highway.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Анализ литературы показал, что наиболее распространенным методом оценки механических потерь в автомобиле -это метод выбега на дороге. Метод выбега автомобиля на стенде с беговыми барабанами используется значительно реже [19].…”
Section: анализ публикацийunclassified